Examen especial a los activos fijos en la Unidad Educativa San Felipe Neri período 2022 - Guanoluisa Paredes, Fabrizio Alexis (2024)
ABSTRACT: The present research work with the topic “Special examination of fixed assets in the San Felipe Neri Educational Unit, period 2022, aims to carry out the practical implementation of the audit phases, which are planning, execution, and communication of results. In Chapter I, the problem that affects the San Felipe Neri Educational Unit related to the component under study, and the general and specific objectives are also determined. Chapter II contains a bibliographic review related to the dependent variable (fixed assets) and independent variable (special examination). Chapter III began with the method, type, and approach of the research, in addition to the various instruments to be used in data collection. Chapter IV presents the results of the application of the phases of the special examination for Fixed Assets in the San Felipe Neri Educational Unit, which concludes with the Audit Report where the most important findings are found, such as the lack of manuals and policies for the management of fixed assets, documents with incomplete information, the auxiliaries of fixed assets are outdated, the accounting balances do not show the reality of the fixed assets and depreciation. Finally, the report has conclusions and recommendations.